Contribution to determination of extracellular DNA origin in the biofilm matrix - Svarcova, Viviana; Zdenkova, Kamila; Sulakova, Martina; Demnerova, Katerina; Pazlarova, Jarmila (Journal of basic microbiology, 2021)
This study is focused on the analysis of extracellular DNA (eDNA) from a biofilm matrix formed by Staphylococcus aureus, Listeria monocytogenes, and Salmonella enterica. The presence of eDNA in the biofilm of all the studied strains was confirmed by confocal laser scanning microscopy using fluorescent dyes with high affinity to nucleic acid. The protocol for eDNA isolation from the biofilm matrix was established, and subsequent characterization of the eDNA was performed. The purified eDNA obtained from the biofilm matrix of all three microorganisms was compared to the genomic DNA (gDNA) isolated from relevant planktonic grown cells. The process of eDNA isolation consisted of biofilm cultivation, its collection, sonication, membrane filtration, dialysis, lyophilisation, and extraction of DNA separated from the biofilm matrix with cetyltrimethylammonium bromide. An amplified fragment length polymorphism (AFLP) was used for comparing eDNA and gDNA. AFLP profiles showed a significant similarity between eDNA and gDNA at the strain level. The highest similarity, with a profile concordance rate of 94.7% per strain, was observed for S. aureus, L. monocytogenes, and S. enterica exhibited lower profiles similarity (78% and 60%, respectively). The obtained results support the hypothesis that the eDNA of studied bacterial species has its origin in the gDNA.
Keywords: Staphylococcus aureus; Extracellular Polymeric Substance Matrix; Salmonella enterica; DNA bakterií; DNA, Bacterial; AFLP; Listeria monocytogenes; extracelulární matrix; matrix extracelulárních polymerních látek; biofilm; extracellular DNA; Extracellular Matrix